EXPLORING THE INTEGRATION OF VIRTUAL REALITY IN PHYSICAL EDUCATION: A COMPREHENSIVE REVIEW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Virtual Reality (VR) has emerged as a promising technology with diverse applications across various domains, including education. In the realm of physical education (PE), VR presents an innovative approach to enhance learning experiences, offering immersive environments and interactive simulations. This study provides a comprehensive review of existing literature to explore the integration of VR in PE, focusing on its efficacy, challenges, and potential outcomes. A systematic search of academic databases, including ProQuest/Web of Science, EBSCO, DOAJ, and Gale databases, was conducted to identify relevant studies published between Jan. 2016 and Feb. 2024. Keywords such as "virtual reality" and “physical education” were used to filter the literature. Studies involving diverse research designs, including experimental trials, case studies, and qualitative analyses, were included in the review. The review revealed a growing amount of literature exploring the integration of VR in PE, highlighting its potential to enhance engagement, motivation, and skill acquisition among students. Studies reported positive outcomes in various systems around the world. VR-based interventions demonstrated effectiveness in improving performance, knowledge retention, and adherence to exercise regimens. Moreover, immersive simulations enabled experiential learning, providing students with realistic scenarios. However, challenges such as equipment cost, technical limitations, and user discomfort were noted as barriers to widespread adoption. Additionally, concerns were raised regarding the potential isolation of students and the need for adequate supervision in VR environments. In conclusion, the integration of VR technology in PE shows promise as a valuable tool to enrich teaching and learning experiences. With continued advancements in technology and pedagogy, VR has the potential to revolutionize PE education, providing students with immersive and interactive learning environments conducive to holistic development.